Research on the re-design application of "Jieshou" colored - Li Bohao; Musnin Bin Misdih (Penerbit Universiti Malaysia Sabah, 2024)
To explore the application strategy of “JieShou” pottery decoration elements in modern cultural and creative production design, to protect the inheritance and development of “JieShou” pottery culture, and to improve the inheritance path of revitalized “JieShou” pottery culture. The paper adopts the theory of shape grammar, combines the literature method, and utilizes computer-aided design to systematically excavate and analyze the depth of “JieShou” colored pottery decorations. The culture of the shape is used to deduce and transform the patterns of “JieShou” colored pottery, obtain new derivative patterns, and apply them to the design of cultural and creative products. A series of innovative derivative patterns of the original patterns of “JieShou” colored pottery have been realized, and these derivative patterns have enriched the traditional visual expression of “JieShou” colored pottery patterns, broadened their cultural dissemination and promotion paths, and also promoted the effective dissemination and living inheritance of China's traditional cultural resources in the contemporary contex.